1986
DOI: 10.1079/bjn19860070
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for the hypocholesterolaemic activity of saponins

Abstract: 1. Saponins are steroid or triterpene glycosides which occur in a number of important food plants, including such staples as soya beans (Glycine max) and chickpeas (Cicer arietinurn). They are known to be hypocholesterolaemic.2. Some saponins form an insoluble complex with cholesterol which prevents its absorption from the small intestine. Others cause an increase in the faecal excretion of bile acids, an indirect route for elimination of cholesterol.3. We have investigated the effects of different saponins on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
115
2
7

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(124 citation statements)
references
References 12 publications
0
115
2
7
Order By: Relevance
“…It has been reported that saponins when supplemented in diets reduce cholesterol content in blood and tissues in monogastric mammals, such as rats, gerbils and humans (Sidhu and Oakenfull, 1986;Potter et al, 1993;Harris et al, 1997). This cholesterol-reducing effect is attributed to saponins ability to form insoluble complexes (micelles) with sterols (Sidhu and Oakenfull, 1986), such as cholesterol and bile acids.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that saponins when supplemented in diets reduce cholesterol content in blood and tissues in monogastric mammals, such as rats, gerbils and humans (Sidhu and Oakenfull, 1986;Potter et al, 1993;Harris et al, 1997). This cholesterol-reducing effect is attributed to saponins ability to form insoluble complexes (micelles) with sterols (Sidhu and Oakenfull, 1986), such as cholesterol and bile acids.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that saponins when supplemented in diets reduce cholesterol content in blood and tissues in monogastric mammals, such as rats, gerbils and humans (Sidhu and Oakenfull, 1986;Potter et al, 1993;Harris et al, 1997). This cholesterol-reducing effect is attributed to saponins ability to form insoluble complexes (micelles) with sterols (Sidhu and Oakenfull, 1986), such as cholesterol and bile acids. Several feedstuff used for livestock feeding, such as Yucca schidigera (Singer et al, 2008;Holtshausen et al, 2009), Quillaja saponaria (Holtshausen et al, 2009), Medicago sativa (Klita et al, 1996) and Sapindus saponaria (Abreu et al, 2004) contain saponins and are used in -E-mail: vvasta@unict.it animal nutrition with the purpose of inhibiting methanogenesis in the rumen (Patra and Saxena, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent years, the saponins containing plants and their effects on human and animal health are one of the most studied area. Several pharmacological properties are attributed to saponins such as immunological adjuvant [5] , anticarcinogenic [6] , hypocholesterolaemic [7] , antifungal [8] , anti-inflammatory and antioxidant [9,10] . Additionally, they are supplemented to poultry diets for decreasing the excrete amonium [11] .…”
Section: Introductionmentioning
confidence: 99%